Information Systems Adoption among SMEs in Developing Country: The Case of Gerbang Kertasusila - Wiradinata, Trianggoro (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2018)
The rapid growth of Internet Technology (IT) in Indonesia opens up many new business process innovations for small and medium enterprises (SMEs). Observing the cost of acquisitioning IT has become more affordable now compared to ten years ago, more and more SMEs convinced to implementing it. However, the success rate has been anecdotal. Various studies in the field of SMEs have been done, but not much focusing on how SMEs are adopting Integrated Information Systems. Specifically, in Gerbang Kertasusila (Industrial part of East Java, Indonesia), most of SMEs are trying to automate their business processes, however not many realize that in terms of IT adoption context, SMEs are not just merely a simple scaleddown model of large firms, hence many project implementations in SMEs were failing. This study combines T-O-E and TAM framework to analyses the important antecedents of technology adoption at the firm level. The collected data of 398 SME owners or managers were tabulated and analyzed using structural equation modelling to measure the causal effects. Result findings from final model confirmed the significance of Competitive Pressure (CP) and Owner’s ICT Knowledge and Innovativeness (OIKI) as the largest predictor of Intention to Adopt IT for business process automation. Despite solid theoretical contribution of the findings, this study also offers practical means of increasing the success rate of IT adoption by SMEs.